Gli atti del Congresso di Karlsruhe del 1860 - D’Auria, Maurizio (Chimica nella Scuola, 2023)
During 1860 in Karlsruhe Kekulè organized an important chemistry congress with the hope to solve some problems related to the nature of atom and molecules. In this congress Stanislao Cannizzaro presented his results collected in the Sunto di un Corso di Filosofia Chimica published on Nuovo Cimento. Here we publish the act of this congress, collected by Anschütz and translated by Michele Giua; the Italian version was published on an almost unobtainable journal. In this act the role of Cannizzaro appears to be relevant and decisive for the results of the congress.